Model Komunikasi Persuasif Dalam Pembelajaran Materi Praktek Sholat Fardu untuk Anak Usia Dini - Bella Anggraini; Aida Efendi; Mutia Azzahra; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Summary Persuasive communication skills are very important for teachers. This research proposes a convincing communication model for learning fardhu prayer practice material in early childhood. This type of research is a case study using a qualitative approach. Data collection techniques use observation, interviews and documentation. Technical Data analysis uses the Spradiley model by conducting domain analysis. The results of the research show that the persuasive communication model is very useful for teachers in learning material on the practice of fadhu prayers for early childhood. To support persuasive communication, teachers need to master the material on fardu prayers according to Tarzi Muhammadiyah, an interesting learning strategy,supporting learning conditions, and supporting keys. Through this research, information was also obtained that audio-visual learning media that applies fardu prayer practices according to the Sunnah is needed to support the persuasive communication model implemented by teachers.